Tracking Groups of Pedestrians in Video Sequences - Marques, Jorge S.; Jorge, Pedro M.; Abrantes, Arnaldo J.; Lemos, J. M. (2003 Conference on Computer Vision and Pattern Recognition Workshop, 2003)
This paper describes an algorithm for tracking groups of objects in video sequences. The main difficulties addressed in this work concern total occlusions of the objects to be tracked as well as group merging and splitting. A two layer solution is proposed to overcome these difficulties. The first layer produces a set of spatio temporal strokes based on low level operations which manage to track the active regions most of the time. The second layer performs a consistent labeling of the detected segments using a statistical model based on Bayesian networks. The Bayesian network is recursively computed during the tracking operation and allows the update of the tracker results everytime new information is available. Experimental tests are included to show the performance of the algorithm in ambiguous situations.